Yield of karyotyping in children with developmental delay and/or dysmorphic features in Sohag University Hospital, Upper Egypt - Sadek, Abdelrahim A.; Mohamed, Mostafa Ashry (The Egyptian journal of medical human genetics, 2018)
Global developmental delay (GDD) represents a measurable lag in a young child's achievement of developmental milestones compared to age matched children. Affection of two or more developmental domains is fundamental for assumption of GDD. Many chromosomal abnormalities are responsible for developmental delay or mental retardation and can be detected using G-banded karyotyping. This work aimed to determine the yield of karyotyping in children with GDD and/or dysmorphic features in Sohag University Hospital, Upper Egypt. All children presenting with GDD and/or dysmorphic features, with abnormal karyotyping or other genetic testing were included. Full history, thorough clinical and detailed neurological examinations were done. The results of other investigations done for the patients, including neuroimaging and electroencephalography (EEG), were utilized (if available). The total number of patients included was 395 patients, out of 646 patients who did karyotype; the mean age of presentation was 24.7 ± 32.1 (SD) months, there were 243 (61.5%) males and 152 (38.5%) females. The positive yield of karyotyping in children with developmental delay and/or dysmorphic features, including classic Down features, was 61.1%; however, with exclusion of Down syndrome and other suspected trisomies, it became 7.4%. The most prevalent chromosomal abnormality was trisomy 21-Down syndrome (364 patients/92.2%), followed by structural chromosomal abnormalities and marker chromosome in 19 patients (4.8%) and, lastly, sex chromosome abnormalities (8 patients/2.0 %). The main complaint was GDD in half of the patients (205/51.9%), while the majority of patients had microcephaly. G-banded karyotyping is a useful tool with reasonable yield in evaluation of children with developmental delay and/or dysmorphic features, especially in countries with limited resources.